Pelatihan Software Mendeley Dalam Peningkatan Kualitas Artikel Ilmiah Bagi Dosen - Rahmawati, Cut; Meliyana, Meliyana; Yuliana, Yuliana; Zain, Helwiyah (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2018)
Publications in international journals and national journals require articles to be written scientifically and use a good reference manager. In this case, there are still many lecturers who have difficulty in writing citations and bibliography. They still undergo manual operating system in changing citations and different styles of bibliographies. This workshop is based on the difficulty of lecturers in publishing their scientific articles in reputable international journals and accredited national journals, especially in writing bibliographies and citations. The workshop was conducted in the form of Mendeley software training on the lecturers' scientific articles. Mendeley software gives a lot of benefit in improving the quality of scientific article writing that is easy for lecturers in writing citations and bibliography. The workshop was held in Abulyatama University involving lecturers from Abulyatama University and other universities such as Serambi Mekkah University and Ar-Raniry State Islamic University. The total number of lecturers who participate in the workshop is 30 lecturers. The ways of workshop delivery are in the form of lectures, practices and frequently asked questions. Surveys were conducted by distributing questionnaires before and after the workshop activities. The results of the workshop show that the lecturers have been able to apply Mendeley in writing citations and bibliography. This workshop gave positive results in improving the lecturers’ ability to write scientific articles. Among the participants' difficulties were in term of Mendeley installation process (6.67 %), the use of it in mobile applications (20 %), and coaching other colleagues (10 %). Approximately 10 % of lecturers feel that they still need additional training for the smoothness use of this application. All lecturers feel that Mendeley is very helpful and will use this application in their publications.